A elaboração de um livro paradidático como proposta metodológica para o ensino de Geografia - Faria, Andressa Carla Nóbrega de Azevedo (2018)
This work consists of a technical-scientific report, and a paradidatic book that deals with the Urban Geography of Timbaúba dos Batistas. Starting by the principle that Geographic Education is based on knowing the local reality and being able to compare with other realities of different scales, we seek with this production to attribute meaning to the knowledge of the place of origin of the students. The textbooks adopted in schools do not contextualize this reality, due to its scale of national coverage. The research developed aims the production of a paradidatic book, directed to the 6th year of the elementary school, which consists of a contribution to the teaching about conceptual approaches on place and landscape. As a result of the research, it was produced from the book titled On the Trails of the City: the urban geography of Timbaúba dos Batistas organized into five chapters that contemplate sociospatial formation, urban configuration, main cultural manifestations, the artistic figure of Elino Julião, and a proposal with suggestions of activities to be developed with students. The writing of this book consists of an effort to contribute to teaching in the perspective of Geographical Education and School Geography, that is, content that assumes importance and meaning for the student by dealing with the reality of the place where their experiences occur, and for the improvement of pedagogical practices.